2018
DOI: 10.2298/sarh171121010b
|View full text |Cite
|
Sign up to set email alerts
|

Does diabetes affect stability in people with unilateral transtibial amputation?

Abstract: Introduction/Objective Currently, analysis of the stability of amputees with diabetes is lacking. The aim of this case study was to examine the effects of unilateral transtibial amputation on the stability and balance confidence of patients with below-knee amputation caused by trauma and diabetes. Methods Seventeen subjects, 12 males and five females, with the average age of 51.47 ± 12.12 years, who use a unilateral transtibial prosthesis, were examined. The balance of 10 traumatic amputees (TTA) and seven dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(16 citation statements)
references
References 23 publications
(25 reference statements)
0
15
1
Order By: Relevance
“…The results from the current study showed a large bias toward recruiting males in research in this area. The reported 26.4% of female lower limb prosthesis users participating in studies was lower than what has been reported in a highly regarded national amputation registry (SwedeAmp; 39%), 234 as well as in previous research (34.5%–38.4%) such as Claessen et al 235 and Ziegler-Graham et al 236 The present authors think it is noteworthy that, of the (n = 161) articles reporting characteristics on sex in the balance articles in Supplemental Table (Supplemental Digital Content 2, http://links.lww.com/POI/A170) 12-14,19-23,25,26,28,29,31-42,44,45,47,48,50-56,58,59,62-69,71-75,77-85,88-90,92,94-102,105-120,122-136,138,140-153,155,157-165,167-179,181-184,186-198,230,231 and the (n = 62) articles of balance confidence, 4,6,8,14,44,71,78,81,83,94,134,138,143,145,147,148,150,151,153,155,157,159,163,165,172,175-178,183,193,196,199-203,205-209,211-229 29.2% and 19.4% respectively, included male sex exclusively. There were only (n = 2) studies with female participants, one balance article 231 and one balance confidence article.…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…The results from the current study showed a large bias toward recruiting males in research in this area. The reported 26.4% of female lower limb prosthesis users participating in studies was lower than what has been reported in a highly regarded national amputation registry (SwedeAmp; 39%), 234 as well as in previous research (34.5%–38.4%) such as Claessen et al 235 and Ziegler-Graham et al 236 The present authors think it is noteworthy that, of the (n = 161) articles reporting characteristics on sex in the balance articles in Supplemental Table (Supplemental Digital Content 2, http://links.lww.com/POI/A170) 12-14,19-23,25,26,28,29,31-42,44,45,47,48,50-56,58,59,62-69,71-75,77-85,88-90,92,94-102,105-120,122-136,138,140-153,155,157-165,167-179,181-184,186-198,230,231 and the (n = 62) articles of balance confidence, 4,6,8,14,44,71,78,81,83,94,134,138,143,145,147,148,150,151,153,155,157,159,163,165,172,175-178,183,193,196,199-203,205-209,211-229 29.2% and 19.4% respectively, included male sex exclusively. There were only (n = 2) studies with female participants, one balance article 231 and one balance confidence article.…”
Section: Discussioncontrasting
confidence: 51%
“…Looking at the protocols and tests, the most commonly found was the Berg Balance Scale, or selected items of the Berg Balance Scale (Figure 2). 14,31,73,80-82,93,94,103,107,118-120,138-140,144,147-168 Timed Up and Go 76,107,117,144,145,148,149,151,162,163,165,169-180 and Limits of Stability tests 12,13,20,25,30,37,42,46,47,59,71,72,74,83,84,89 were common (Figure 2). One leg stance test appeared with various names in about some studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations